Double-strand break repair in Ku86- and XRCC4-deficient cells. - Kabotyanski, E B (1998)
The Ku86 and XRCC4 proteins perform critical but poorly understood functions in the repair of DNA double-strand breaks. Both Ku 86- and XRCC4-deficient cells exhibit profound radiosensitivity and severe defects in V(D)J recombination, including excessive deletions at recombinant junctions. Previous workers have suggested that these phenomena may reflect defects in joining of the broken DNA ends or in protection of the ends from nucleases. However, end joining in XRCC4-deficient cells has not been examined. Here we show that joining of both matched and mismatched DNA ends occurs efficiently in XRCC4-deficient cells. Furthermore, analysis of junctions shows that XRCC4 is not required to protect the ends from degradation. However, nucleotide sequence analysis of junctions derived from joining of mismatched DNA ends in XRCC4-deficient cells revealed a strong preference for a junction containing a 7 nt homology. Similar results were obtained in Ku86-deficient cells. These data suggest that in the absence of XRCC4 or Ku86, joining is assisted by base pairing interactions, supporting the hypothesis that these proteins may participate in aligning or stabilizing intermediates in end joining.